Evaluation of Osteogenic property of methanolic extract of the root, leaf and whole plant of Tridax procumbens linn in Wistar albino rats (Journal of Pharmaceutical Negative Results, 2023)
The objective was to evaluate the osteogenic property of methanolic extract of Tridax procumbens linn (TP) in Wistar albino rats using radiological, histopathological and histomorphometric analysis. 24 Wistar albino rats were divided into 4 groups with 6 rats in each group. Rats were anesthetized with 10% ketamine and 2% xylazine and bone defect of 3 mm size was induced in all the animal’s right tibia using dental drill. Rats in group 1 were not given any treatment and served as control, rats in group 2 received methanolic root extract of TP 200 mg/kg PO, rats in group 3 received methanolic leaf extract of TP 200 mg/kg PO, and rats in group 4 were received methanolic whole plant extract of TP 200 mg/kg PO. All the animals were sacrificed on day 28, the treatment was continued till the animals were sacrificed. It was noted that the root, leaves and whole plant methanolic extracts of TP have caused bone repair of the defects induced in Wistar albino rat’s tibia in terms of mineralization and new bone formation. Among the three extracts, the whole plant extract has more bone regeneration effect. No mortality was seen in any of the groups. Hence the whole plant extract of TP can be a promising prospective therapeutic agent for bone repair.